(3GdCHYGO hGdCLQGes - (3chTjGQ Hf dHGf GdLjdj, CHh GdMSf,J (B350 (3g` s
(3ChdgG (B:s
(3Efi QCjJ CcKQ GdfGS bO ESJeQ Ydi SeYge bhd GdefLejf (B: (3Ef GdchGcH ai HQL cPG hOQLI cPG , hEf GdcSha ai hbJ cPG hcPG s
(3BNQgG (B:s
(3agPg ebGOjQ GdCHYGO hGdCLQGe , hGdWQjb Edi GdhUhd EdjgG hef HYO Cf hajfG HeG hYO ai UOQ GdebGdI GdebGdI, aEfG fNJe GdebGdI JeJ GdebGdI ai GdCHYGO hGdCLQGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B5s
(3HgG QShe gfOSjIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B148 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B838s
Keywords: (3Gdadcs